1999
DOI: 10.1172/jci4431
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the insulin 2 gene induces diabetes with severe pancreatic β-cell dysfunction in the Mody mouse

Abstract: Diabetes is a major public issue due to its high prevalence and long-term complications (1). The molecular pathogenesis of diabetes, however, remains largely unknown. The common forms of diabetes are syndromes with heterogeneous etiologies, each of which is influenced by polygenic and multiple environmental factors. Therefore, genetic and pathophysiologic analysis of diabetes remains a major challenge. On the other hand, recent progress in the identification of genetic alterations in monogenic disorders has pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
541
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(562 citation statements)
references
References 27 publications
18
541
0
3
Order By: Relevance
“…In addition, mitochondrial swelling was observed in these beta cells. ER abnormality appears to be a common finding in rodent models of ER stress-related beta cell failure [26,29,30]. Riggs et al reported similar findings in their beta cellspecific Wfs1 knockout mouse [22].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, mitochondrial swelling was observed in these beta cells. ER abnormality appears to be a common finding in rodent models of ER stress-related beta cell failure [26,29,30]. Riggs et al reported similar findings in their beta cellspecific Wfs1 knockout mouse [22].…”
Section: Resultsmentioning
confidence: 72%
“…If the stress is severe, apoptosis is induced. Accumulating evidence suggests that a high level of ER stress or defective ER stress signalling causes beta cell death and that diabetes thereby develops [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…However, the phenotype of Akita mouse is not only due to the loss of insulin, but rather due to gain of function, because single Ins1 or Ins2 knockout mice do not develop diabetes. 89 We found that disruption of the CHOP gene markedly delayed the onset of disease in heterozygous Akita mice. 59 This indicates that progressive hyperglycemia in Akita mice is caused by b-cell apoptosis through CHOP induction.…”
Section: Diabetesmentioning
confidence: 81%
“…The simple assumption is that a defect in ER functionality, generated during ER stress induction, may prevent translation, folding, and processing of proinsulin, and may lead to a secretion defect of insulin [31]. Several reports have shown that the induction of ER stress using mis-folding mutants, PERK deficient mutants, and hyper-phosphorylation of eIF2a, could elicit defective processing of secretory proteins and reduced mobilization of secretory vesicles [31][32][33]. However, our data showing that the basal secretion of insulin was gradually increased in accordance with an increased dose of palmitate suggests that a fundamental defect of proinsulin-processing or granule-exocytosis may not be involved in palmitate-induced GSIS-inhibition.…”
Section: Discussionmentioning
confidence: 99%